2016
DOI: 10.1039/c6ra02680j
|View full text |Cite
|
Sign up to set email alerts
|

An amperometric glucose biosensor based on a MnO2/graphene composite modified electrode

Abstract: In this paper, a novel composite of graphene/MnO 2 (GR/MnO 2 ) was successfully synthesized by a simple one-step hydrothermal method. The as-synthesized MnO 2 and the composite were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR). The results showed that MnO 2 was nanorods and the two materials were perfectly composited. The composite was decorated on a glassy carbon electrode (GCE) and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 59 publications
0
17
0
2
Order By: Relevance
“…The sensitivity and LOD of the fabricated electrode are compared to various electrodes as shown in Table II. 11,18,28,29,[53][54][55][56][57][58] Most of the electrodes in the review have high sensitivity and good LOD as they used thick GO prepared by a modified Hummers method. Our electrode shows sensitivity and LOD similar to results by Palanisamy et al 18 which used thick GO hybridized with MWCNT and supported by glassy carbon electrode (GCE) that demonstrated high thermodynamic surface adsorption 59 and specific thermodynamics adsorption and redox reduction mechanism with GOx.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity and LOD of the fabricated electrode are compared to various electrodes as shown in Table II. 11,18,28,29,[53][54][55][56][57][58] Most of the electrodes in the review have high sensitivity and good LOD as they used thick GO prepared by a modified Hummers method. Our electrode shows sensitivity and LOD similar to results by Palanisamy et al 18 which used thick GO hybridized with MWCNT and supported by glassy carbon electrode (GCE) that demonstrated high thermodynamic surface adsorption 59 and specific thermodynamics adsorption and redox reduction mechanism with GOx.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, MnO 2 had attracted much focus because of its low cost, good for easy synthesis, and so on. [110] Among some kinds of MnO 2 , particularly, polymorphs, α-MnO 2 was widely used because of its big tunnel structure and MnO 6 octahedral unit, [111] but the low conductivity of MnO 2 (10 À 5 to 10 À 6 S/cm) hindered its use. Baruah et al [112] obtained PEDOT: PSS/MnO 2 /rGO, and it had a better current density was 56.38 mA/cm 2 and initial potential was low (0.32 V) for MOR.…”
Section: Other Transition Metal Catalystsmentioning
confidence: 99%
“…In addition to the widespread use of metals such as Pt, Ni, other transition metals and these transition metal oxides also had potential as catalysts for MOR. Among them, MnO 2 had attracted much focus because of its low cost, good for easy synthesis, and so on [110] . Among some kinds of MnO 2 , particularly, polymorphs, α‐MnO 2 was widely used because of its big tunnel structure and MnO 6 octahedral unit, [111] but the low conductivity of MnO 2 (10 −5 to 10 −6 S/cm) hindered its use.…”
Section: Classification Of Catalystsmentioning
confidence: 99%
“…More studies have reported the use of rGO as a template for synthesizing nanocomposite nanomaterials for glucose biosensor fabrication; for example, a NiCo2O4/nitrogen-doped rGO [126], copper sulfide nanoflake-rGO [127], Cu2O/rGO [128], Cux@Ni100-x core-shell NPs-rGO [129], Ni NPs-rGO [130], 3D rambutan-like CuO and CuO/rGO [131], Au NPdecorated GO [132], NiO NPs-MW-CNTs-rGO [133], MnO2/graphene [134], and polydopamine/ZIF-8@rGO [135]. Although they exhibit improved performances, control over the size of nanomaterials and uniformity in supporting rGO remain challenging.…”
Section: Accepted Manuscriptmentioning
confidence: 99%